EFFORTS TO IMPROVE THE HEALTH AND SAFETY OF WORKERS AS A STEP TO ACCELERATE ACHIEVING THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN RINGINSARI VILLAGE, KEDIRI REGENCY - Irianingtyas, Riza; Rahmania, Nima Eka Nur; Budiarti, Tamara Nur; Jariyah, Mufidatul; Maryiantari, Ellyza Setya; Tigowati; Kuncoro, Achmad; Nuwa, Geovania Nage; Ghina, Aprilia Dhia (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Counseling activities were given to all workers in the home industry of gadung chips in Ringinsari Village, Kandat District, Kediri Regency, as a form of community service in the form of delivering materials and simulations that are expected to increase workers' awareness of health and safety in the workplace. The counseling activities were carried out in September at the home of the industry owner. Before carrying out the counseling activities, there was a preparation process for approximately four weeks before the implementation of the activity, starting from determining the type of activity to submitting permits to the relevant parties. As a form of evaluation, this activity was attended by all workers and owners of gadung chips businesses, the participants participated in the activities with great enthusiasm and the counseling guidance activities ran smoothly.